The Business of leadership;An Introduction - Bowerman,Karen Dill (Yes Dee, 2010)
Specifically tailored to business students, this undergraduate textbook features a "how-to" approach and is filled with with current, lively examples and well-crafted learning tools. It takes readers from the kind of leradership they can exhibit in supervisory roles to the visionary leadership they must exhibit in management and executive roles.